UPAYA PERLINDUNGAN KONSUMEN MUSLIM DAN NON-MUSLIM MELALUI SERTIFIKASI HALAL DAN TRANSPARANSI KOMPOSISI PRODUK MAKANAN - Tutik Nurul Janah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2020)
The purpose of consumer protection rules is to improve protection against consumers by avoiding the negative effects. Halal certification requirements on food products are also a country protection effort against consumers. Consumers have the right to know the content of food and beverages they will consume. During this time, halal certification is synonymous with Muslim community needs. However, it is not only Muslims who have religious rules regarding food. For example, Christians and Hindus also have rules regarding food. Indonesia as a multicultural-multireligious country, should attention to this diversity. If the certification of halal products only targets the needs of Muslims only, then how with non-Muslim consumer protection efforts related to their right to know the content of food, cosmetics and medicines are not contradictory Their religious. This research is a research library with a normative juridical approach. This research aims to give readers an understanding of the principles related to halal certification, especially on food products. The research is also important to provide an understanding of the relationship between halal certification and transparency of food product composition with the fulfillment of Muslim and non-Muslim consumer rights.